Genistein Attenuates Lipopolysaccharide-Induced Hepatic Oxidative Stress and Inflammatory Responses in Turbot (Scophthalmus maximus L.) Juveniles - Xiao-qian Zhou; Zi-yan Shi; Hai-hong Chen; Xin Xiao; Dan Xu; Zhi-jie Dan (Aquaculture Nutrition)
The antioxidant and anti-inflammatory functions of genistein (GEN) and the regulatory mechanisms have been intensively investigated in mammals; however, there was a paucity of studies in aquatic animals. The purpose of this study was to evaluate the effects of GEN on lipopolysaccharide (LPS)-induced hepatic oxidative stress and inflammatory responses in turbot (Scophthalmus maximus L.) juveniles. Turbots (20 g body weight) were intraperitoneally injected with PBS (the Control group), LPS (50 μg/g), and LPS (50 μg/g) + GEN (0.05, 0.5 and 5 μg/g), respectively. Results showed that the content of the total bilirubin, the activities of the alanine aminotransferase, aspartate aminotransferase, γ-glutamyl transpeptidase, and alkaline phosphatase were significantly decreased with increasing levels of GEN injection (p<0.05). Results exhibited that hepatic proinflammatory factors, oxidative stress-related factors, and apoptotic factors mRNA expression were significantly upregulated after intraperitoneal injection of LPS in turbot, compared with the Control group (p<0.05). Meanwhile, the mRNA expressions of these apoptosis- and inflammation-related factors showed significant linear or quadratic terms of downregulation with increasing levels of GEN injection (p<0.05) and almost reached the lowest values at 0.5 μg/g or 5 μg/g of GEN injection levels. The symptoms of LPS-induced disorganization of hepatocyte arrangement, vacuolization of hepatocytes, and inner mitochondrial cristae damage in turbot were significantly improved after GEN injection. Furthermore, the main signaling pathways associated with inflammation included Herpes simplex virus 1 infection, RIG-I-like receptor, NOD-like receptor, C-type lectin receptor, and p53 signaling pathways. Moreover, results of weighted correlation network analysis indicated that vascular endothelial growth factor A–A (vegfaa) and signal transducer and activator of transcription 3 (stat3) were likely to be hub genes. Meanwhile, mRNA expressions of vegfaa, vegfab, stat1, stat2, stat3, stat4, stat5a, and stat5b exhibited significantly linear or quadratic downregulation with increasing levels of GEN injection (p<0.05). The above results confirmed that intraperitoneal injection of GEN significantly alleviated LPS-induced hepatic oxidative stress and inflammatory injury in turbot, and vegfaa and stat3 possibly play a key role in this process.